2002
DOI: 10.1128/cdli.9.4.747-752.2002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Presence of Immune Dysfunction in Chronic Fatigue Syndrome

Abstract: Chronic fatigue syndrome is a medically unexplained ailment characterized by new onset of fatigue accompanied by rheumatological, infectious, and neuropsychiatric symptoms. Because the ailment often begins suddenly with a flu-like presentation, early pathophysiological ideas as to cause included viral infection and immune activation. When early reports identified putative immunological abnormalities in this illness, it was given the name of chronic fatigue and immune dysfunction syndrome, or CFIDS.The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 72 publications
4
65
1
Order By: Relevance
“…However, two groups have reviewed the literature and have concluded that insufficient evidence exists to support that hypothesis (14,16). If some CFS patients had an unrecognized encephalopathy, we reasoned that we might find evidence for immune dysfunction in spinal fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two groups have reviewed the literature and have concluded that insufficient evidence exists to support that hypothesis (14,16). If some CFS patients had an unrecognized encephalopathy, we reasoned that we might find evidence for immune dysfunction in spinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…In two plasma cytokine studies using classical statistical methods, we found no differences in immune variables between CFS patients and sedentary, age-and sex-matched controls (10,17). In fact, a recent comprehensive analysis of all controlled studies on immune function in CFS found little evidence to support the immune dysfunction hypothesis (16).…”
mentioning
confidence: 91%
“…Investigations into a possible autoimmune component in CFS have shown an increase in the number of B cells of the CD20lCD5 phenotype (7) -a situation normally associated with the production of autoantibodies -and, in the same group of patients, an increase in the expression of CD2 ligand for retroviruses (8). In a 1996 study, 52% of patients with CFS were found to produce autoantibodies directed against nuclear components (9-10).…”
Section: Pathogenesismentioning
confidence: 99%
“…Two findings fostered this idea: first, approximately a third of CFS patients report a sudden, influenza-like onset of their illness (37), and second, administration of proinflammatory cytokines leads to many of the same symptoms seen in CFS (26). However, we recently reviewed the literature on this hypothesis and found relatively little empirical data to support it (20); a more recent small study did report higher levels of one such cytokine, serum transforming growth factor ␤, in patients than in controls (35); however, another group did not confirm this result (30). Other work extending the research to cellular production of proinflammatory cytokines was also negative (1).…”
mentioning
confidence: 96%